ANALYZING ATTITUDINAL FACTORS AND THEIR RELATION TO LANGUAGE LEARNING (AQUANTITATIVE RESEARCH CONDUCTED IN ONE OF THE CLASSES AT STBA X - TANGERANG) - SANTOSA SANTOSA (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2018)
This research is a simple research conducted only to one class of STBA X– Tangerang with 10 students as the subjects of research taken as purposive sampling. This research aims at knowing the relation between the students’ attitude and their accomplishment in English, as well as the other supporting factors of their attitude and lastly attitudinal effect on the students’ learning goal is also explored. Research found that basically the students’ positive attitude (showing in the written scale) has a quite positive impact on their accomplishment despite the fact the data taken are only the last semester test, however from the students’ response, it is clear that they have a quite positive attitude which can probably affect their learning result. It is high time for teachers, parents and other sources who are proven influential to the students’ progress, to always support their students so that the students can always have positive attitude in their learning foreign language, due to their continuous discussion with their teacher or parents rather than absorbing irrelevant information which can possibly affect the children attitude thus jeopardizing their learning process.